ESTUDO COMPARATIVO DA RECRISTALIZAÇÃO NOS AÇOS SAE 1006 E ARBL LNE 380 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The recrystallization study is of fundamental importance in the thermomechanical processing of metals and alloys, since the grain refinement can be obtained affecting the final microstructure. Understanding the behavior of alloys during the mechanical hardening and subsequent annealing is of fundamental importance for the control of their microstructure and final properties. This paper has as main objective a comparative study between the steel SAE 1006 and LNE 380 during processing involving cold rolling and annealing subsequent. And also analyze the influence following the rolling passes in the texture of the material. For this, the two steel samples were cold rolled by 50% and 70% reduction in thickness corresponding to true strain values of 0.7 and 1.2, respectively. Following the samples were annealed in metal bath, and then characterized by optical microscopy, scanning electron microscopy (SEM and FEG), hardness Vickers, texture analysis by x-ray diffraction and EBSD. The LNE 380 steel samples, due to the larger number of particles has undergone further hardening the SAE 1006 steel during cold rolling. In the deformation texture both steels showed partial fiber and fiber , but for the LNE 380 steel fibers are more developed. The LNE 380 steel was laminated with different sequence for the same deformation, and the sequence with more and less passes show texture more intense compared with a sequence of intermediate passes. SAE 1006 steel was recrystallized from shorter times and temperatures that LNE 380 steel, since this has a large number of particles which impede the recrystallization because they act as a barrier to the movement of grain boundaries.
Keywords: aço microligado; laminação; recristalização; textura; microestrutura; microalloyed steels; rolling; recrystallization; texture; microstructure; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA